IDENTIFIKASI JALUR PEMASARAN SAPI BALI DI PASAR TERNAK TRADISIONAL - Jeflan Halidu; Yanti Saleh; Fahrul Ilham (Jambura Journal of Animal Science, 2021)
This study aims to analyze the marketing channels and marketing margins of Bali Cows in traditional markets. This research was conducted from April to December 2019. A qualitative descriptive method was used in this research. Primary data collection through surveys based on interviews and observations at the respondent level, and secondary data obtained from relevant stakeholders. The results showed that there are 3 channels, namely Channel I, namely Farmer-Consumer (P-PL-K), Channel II are Farmer - Local Trader - Consumer (P-PL-K), and Channel III are: Farmer- merchant collector - Trader retailer-Consumer (P-PP-Pp-K). The marketing margins for breeders, collectors and retailers are: Rp. 0., Rp. 1,000,000 and Rp. 500,000